Traditional Chinese medicine Dingkun pill to increase fertility in women with a thin endometrium—a prospective randomized study - Jin, Fengyu; Ruan, Xiangyan; Qin, Shuang; Xu, Xin; Yang, Yu; Gu, Muqing; Li, Yanqiu; Cheng, Jiaojiao; Du, Juan; Yin, Xiaodan; Mueck, Alfred O. (Frontiers in Endocrinology, 2023)
Objective: To optimize the treatment methods of infertility which is suggested to be mainly caused by thin endometrium using a special form of Traditional Chinese Medicine, the Dingkun pill (DKP), to increase the beneficial endometrial effect of conventional hormone/progestogen therapy.Methods: 307 patients visiting our specialized gynecological endocrinology department because of infertility, which we suggested to be caused by thin endometrium (endometrial thickness (EMT) < 7 mm), were randomly assigned to the TCM to thin endometrium infertility experimental group and a control group. The experimental group was treated with estradiol + sequential dydrogesterone + DKP (every day); the control group received hormonal treatment without the Chinese medicine. All patients were monitored in terms of follicle diameter, EMT and endometrial type every 2 days from the 8-10 th day of the menstrual cycle until ovulation day during three menstrual cycles. Serum progesterone levels on 7-8 days after ovulation were measured and the cumulative pregnancy rate during 3 menstrual cycles between the two groups was compared.Results: EMT on ovulation day in the experimental group was significantly higher than in the control group (7.88 vs. 7.15 mm; p< 0.001). Proportion of type A and B endometrium in total was significantly higher than in control group (83.2% vs. 77.7%; p<0.05). Progesterone levels were significantly higher than those in the control group (10.874 vs. 10.074 ng/mL; p< 0.001). The cumulative pregnancy rate, main outcome of the study, was significantly higher than in the control group (29.2% vs. 15.7%; p < 0.05).DKP added to conventional estrogen/progestogen therapy can significantly improve EMT and luteal function in patients attending due to infertility.Because this regimen increased the cumulative pregnancy rate in our study, we conclude that DKP can be used to increase so called "thin endometrium infertility".